The Consequences of the 2017 US International Tax Reform: A Survey of the Evidence - Dhammika Dharmapala (Center for Economic Studies and ifo Institute (CESifo), 2023)
The 2017 US tax legislation - widely referred to as the Tax Cut and Jobs Act (TCJA) - fundamentally transformed the US system of international taxation. It ostensibly ended worldwide taxation but introduced, for instance, a new tax on "Global Intangible Low-Taxed Income" (GILTI). This paper surveys the emerging empirical literature on the impact of the TCJA's international provisions. It documents five robust findings in this empirical literature. First, the TCJA led to a general decline in US MNCs' foreign acquisitions. Second, the TCJA increased US MNCs' investment in routine foreign tangible assets. Third, the reform did not lead to any change in profit shifting by US MNCs beyond the magnitude that would be expected based on the TCJA's tax rate reduction. Fourth, The TCJA appears to have reduced the market value of US MNCs relative to domestic US firms. Fifth, the TCJA does not appear to have had any detectable impact on domestic US investment and wages (although there are some contrary results for capital expenditures). The welfare implications of these findings depend crucially on whether US MNCs' are viewed as having engaged in too much or too little foreign activity prior to the TCJA. This depends on the choice of theoretical framework and the relevant normative benchmark, and cannot readily be resolved empirically.
Keywords: H25; F23; 330; international taxation; multinational firms; Tax Cut and Jobs Act (TCJA); repatriation taxes; global intangible low-taxed income tax